Transportation of the U.S. Forces in the occupation of Iceland, 1941-1944. - Dunham, H.H.; Historical Unit, Office of the Chief of Transportation, Army Service Forces (1945)
This monograph was prepared prior to October 1946 from documentary material then available. It is not to be considered a final report, therefore, nor has it been thoroughly edited. Reproduction has been authorized in order that the information may be made available to military schools pending the publication of the official history of the Transportation Corps. The document contains maps, charts, illustrations, and photographs. [This archival item was stapled- and some pages appear out of order- but was scanned as originally constructed.]